IS THERE A DIFFERENCE BETWEEN THE DYSMENORRHEA EXPERIENCES OF GENERATIONS? - NACAR, Gülçin; ÜNVER, Hacer; TİMUR TAŞHAN, Sermin (Göbeklitepe Medical Science Journal, 2021)
Aim: This study aims to identify the differences between the dysmenorrhea experiences of generations. Methods: This descriptive study was conducted in the Nursing Faculty of a public university in a city located in eastern Turkey. The sample was composed of 145 female students who were enrolled in the stated Nursing Faculty and these students’ mothers (n:144) and sisters (182). Data were collected through the Participant Information Form. Data analyses included percentages, means, and Chi-square. Findings: Of all the participants, 30.6% were Generation X, 30.8% were Generation Y, and 38.6% were Generation Z. While 46.3% of Generation X had dysmenorrhea complaint since menarche, 55.7% of the Generation Y and 47.2% of the Generation Z experienced dysmenorrhea since menarche (p:0.001). Besides, 51.2% of Generation X, 52.3% of the Generation Y, and 42.4% of Generation Z reported to experience dysmenorrhea in the first day of menstruation (p:0.035). Generation Y and Z tried to eliminate dysmenorrhea more than Generation X. The majority of Generation X and Y took pain killers to relieve dysmenorrhea, and Generation Z was found to use methods apart from medicine such as resting, massaging the abdomen, and exercising (p<0.05). Dysmenorrhea was found to prevent the daily activities and communication/relationships of Generation Y and Z more than Generation X (p: 0.001). Conclusion: Dysmenorrhea was found to demonstrate differences between the generations in terms of menarche, menstruation duration, coping with dysmenorrhea and the methods used, and preventions in daily activities and communication/relationships.